Evaluating the effectiveness of integrated care in targeted therapy for patients with chronic lymphocytic leukemia - Liu, Xin; Chen, Wumin; Wang, Meiying; Gao, Yan; Kou, Xueqin; Pan, Xianna; Zhang, Lijuan (Frontiers in Oncology, 2025)
BackgroundFor patients with chronic lymphocytic leukemia (CLL), the type of nursing care during targeted therapy may significantly impact treatment efficacy and quality of life. This study evaluated the effects of routine care and comprehensive care on biomarkers, treatment response, and patient-reported outcome measures (PROMs) in patients with CLL undergoing targeted therapy.MethodsA total of 260 patients with CLL were enrolled, with 150 receiving routine care and 110 receiving comprehensive care. Baseline characteristics of the two groups were compared, and differences in biomarkers at diagnosis were assessed. Multivariable logistic regression models were used to analyze the impact of baseline information and care methods on treatment response. Generalized estimating equations (GEE) were used to evaluate trends in PROMs (SF-36, ECOG, and HADS scores) over the follow-up period.ResultsBaseline analysis showed no significant differences between the two groups in terms of age, gender, smoking, alcohol consumption, comorbidities, and Rai stage. Drug response analysis showed that age, diabetes, Rai stage and nursing mode significantly affected the treatment effect. Comprehensive nursing significantly increased the effectiveness of targeted drug therapy and reduced the risk of disease progression. During the follow-up period, the lymphocyte count, white blood cell count, ESR, β2-microglobulin, and LDH levels of patients in the comprehensive nursing group significantly decreased, while immunoglobulin levels significantly increased. In addition, comprehensive nursing significantly improves patients’ quality of life, improves physical fitness, reduces anxiety and depression levels, especially in the six months and one year after treatment.ConclusionComprehensive care significantly improved treatment outcomes, reduced disease progression, and enhanced the quality of life in patients with CLL undergoing targeted therapy, making it suitable for long-term management of patients with CLL.